Developing a Framework for Drawing a Strategy Map by Using the Combination of SWOT, QSPM and DEMATEL Methods (Case Study of Nasb Niroo Company) - Milad Shahsavari; Seyed Hamed Mousavi Rad (مدیریت مهندسی و رایانش نرم)
The aim of this research is to develop a combined framework to to determine strategy map for companies. In this paper the framework is applied to determine the map strategy of Nasb Niroo Company which is one of the sub-organizations under the Mapna holding group. Nowadays, mangers found out that human resources are the main capital of organizations. Nasb Niroo Company aims to use this capital and select best strategies for its objectives. This research focused on assessing the internal and external factors and selecting the best strategies for this company. After selecting the best strategies, the strategy map of company based on the balanced scorecard is developed. This strategy map can help mangers to understand the company’s strategies and its implementation. Finally, the relationships in the strategy map have been evaluated by DEMATEL method. The effective and affected factors are high quality of work and the growth of company’s profit, respectively.